2020
DOI: 10.18103/mra.v8i6.2125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Energy and Macronutrient Cycling on Weight Loss, Body Composition, and Markers of Health in Obese Women Participating in a Resistance-Based Exercise Program

Abstract: To determine whether adherence to a repeating 30-d non-linear diet intervention while participating in a supervised exercise program that includes resistance-exercise would promote weight and fat loss without weight loss plateau and whether alterations in carbohydrate and protein intake may influence results.Methods: Fifty sedentary and obese pre-menopausal females (35.2±7.6 years; 88.7±18 kg, 32.6±6 kg/m 2 , 42.5±4.2% fat) were randomly assigned to an exercise-only (EX) or EX plus diets containing higher prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…However, the CV intervention led to a greater decrease in fat mass and a greater increase in lean mass, resulting in a significant improvement in body fat percentage. Present findings agree with previous studies conducted by our group [10][11][12][13][14][15][16][18][19][20][21][22], which found that individuals participating in this program observed significant reductions in body mass, fat mass, BMI, and waist circumference while preserving lean body mass and resting energy expenditure. Additionally, that adherence to a more structured diet plan promoted less energy intake with a greater proportion of dietary protein intake [17].…”
Section: Primary Outcome-weight Loss and Body Compositionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, the CV intervention led to a greater decrease in fat mass and a greater increase in lean mass, resulting in a significant improvement in body fat percentage. Present findings agree with previous studies conducted by our group [10][11][12][13][14][15][16][18][19][20][21][22], which found that individuals participating in this program observed significant reductions in body mass, fat mass, BMI, and waist circumference while preserving lean body mass and resting energy expenditure. Additionally, that adherence to a more structured diet plan promoted less energy intake with a greater proportion of dietary protein intake [17].…”
Section: Primary Outcome-weight Loss and Body Compositionsupporting
confidence: 93%
“…Consistent with current findings, adherence to the WW program has been reported to promote reductions in body weight, fat mass, BMI, and waist circumference, though the preservation of lean body mass has not been demonstrated [40,41]. Both groups lost over 5% body weight in the 16-week period, which agrees with previous research evaluating adherence to these diets for 12 weeks to 12 months in duration [18,21,[42][43][44][45][46][47][48][49][50][51]. This level of weight loss can be defined as clinically meaningful if maintained one year after treatment [52].…”
Section: Primary Outcome-weight Loss and Body Compositionsupporting
confidence: 89%
See 3 more Smart Citations